Dialogue: The Way of Being Church Today - Parappally, Jacob (Asian Horizons, 2025)
This article argues that dialogue is essential to the identity and mission of the Church today. Tracing the historical development of the Church’s attitude towards other religions—from exclusivism and superiority to recognition and dialogue—it highlights the importance of an open, humble approach. Drawing on the insights of Kuncheria Pathil and Church documents, the author argues that interreligious and intrareligious dialogue is not merely supplementary to evangelisation but an essential part of the Church’s very nature. Through dialogue, the Church advances the Kingdom of God by fostering mutual understanding, reconciliation, and collaborative action for a more human and just world.